Termination of graphene edges created by hydrogen and deuterium plasmas. (25th January 2023) - Ochi, Taisuke; Kamada, Masahiro; Yokosawa, Takamoto; Mukai, Kozo; Yoshinobu, Jun; Matsui, Tomohiro
Abstract: Edge engineering is important for both fundamental research and applications as the device size decreases to nanometer scale. This is especially the case for graphene because a graphene edge shows totally different electronic properties depending on the atomic structure and the termination. It has recently been shown that an atomically precise zigzag edge can be obtained by etching graphene and graphite using hydrogen (H) plasma. However, edge termination had not been studied directly. In this study, termination of edges created by H-plasma is studied by high-resolution electron energy loss spectroscopy to show that the edge is sp 2 bonded and the edge carbon atom is terminated by only one H atom. This suggests that an ideal zigzag edge, which is not only atomically precise but also sp 2 bonding, can be obtained by H-plasma etching. Etching of the graphite surface with plasma of a different isotope, deuterium (D), is also studied by scanning tunneling microscopy to show that D-plasma anisotropically etches graphite less efficiently, although it can make defects more efficiently, than H-plasma. Graphical abstract: